2010
DOI: 10.1074/mcp.m110.001057
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Salivary Secretory Peptidome Profile in Children Affected by Type 1 Diabetes

Abstract: The acidic soluble fraction of whole saliva of type 1 diabetic children was analyzed by reversed phase (RP) 1 -HPLC-ESI-MS and compared with that of sex-and age-matched control subjects. Salivary acidic proline-rich phosphoproteins (aPRP), histatins, ␣-defensins, salivary cystatins, statherin, proline-rich peptide P-B (P-B), betathymosins, S100A8 and S100A9*(S100A9* corresponds to S100A9 vairant lacking the first four amino acids), as well some naturally occurring peptides derived from salivary acidic proline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 49 publications
2
59
0
1
Order By: Relevance
“…In the youngest patient group S100A7 (D27) was the most represented member of the S100A family proteins, together with S100A9 that was detected in the following different isoforms: short, short phosphorylated (at Thr-108 residue), and long S-glutathionylated at the Cys-2 residue (26). Part of the S100A9 short forms were oxidized at the Met-89 residue (19). A comparison between age 18 -50 yr DS subjects and controls showed a statistically significant different level of both S100A9 short phosphorylated and nonphosphorylated isoforms (p values 0.04 and 0.05, respectively).…”
Section: Top-down Proteomics Of Saliva From Down Syndrome Subjectsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the youngest patient group S100A7 (D27) was the most represented member of the S100A family proteins, together with S100A9 that was detected in the following different isoforms: short, short phosphorylated (at Thr-108 residue), and long S-glutathionylated at the Cys-2 residue (26). Part of the S100A9 short forms were oxidized at the Met-89 residue (19). A comparison between age 18 -50 yr DS subjects and controls showed a statistically significant different level of both S100A9 short phosphorylated and nonphosphorylated isoforms (p values 0.04 and 0.05, respectively).…”
Section: Top-down Proteomics Of Saliva From Down Syndrome Subjectsmentioning
confidence: 92%
“…1. Characterization of these proteins, mainly based on the RP-HPLC-ESI-MS and Tandem/MS analysis, has been previously described by some of us (13)(14)(15)(16)(17)(18)(19)(20)(21). Cystatin C and its sulfoxide derivative on methionine 14 were confirmed in the present study by high resolution HPLC-ESI-MS/MS analysis of trypsin digestion products and data are reported in supplemental Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been shown that the susceptibility to and severity of periodontal diseases are increased in patients with diabetes mellitus (19). Indeed, the expressions of antimicrobial peptide, statherin, proline-rich peptides, or histatin, are decreased in diabetic patients (2). Therefore, the production of hCAP-18/LL-37 might be an important marker for the progression of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] We have previously reported the analysis of the salivary proteome in type 2 diabetes, which identified a number of differentially abundant proteins, many of which were glycoproteins whose abundance was altered in prediabetes and diabetes. 34 Alterations in the salivary proteome and peptidome have recently been also reported in type 1 diabetes, 35 with changes in glycoproteins seen in that study as well. In this study, we combine these 2 concepts and describe the utility of a new technology to measure salivary glycoprotein levels for short-term, noninvasive assessment of glycemia.…”
mentioning
confidence: 79%